2002
DOI: 10.1242/jcs.00181
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular targeting of metabolic enzymes to titin in heart muscle may be mediated by DRAL/FHL-2

Abstract: During sarcomere contraction skeletal and cardiac muscle cells consume large amounts of energy. To satisfy this demand, metabolic enzymes are associated with distinct regions of the sarcomeres in the I-band and in the M-band, where they help to maintain high local concentrations of ATP. To date,the mechanism by which metabolic enzymes are coupled to the sarcomere has not been elucidated. Here, we show that the four and a half LIM-only protein DRAL/FHL-2 mediates targeting of the metabolic enzymes creatine kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
245
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(252 citation statements)
references
References 88 publications
3
245
1
3
Order By: Relevance
“…Because FHL2 has been shown to be implicated in the transmission of Rho-induced signals (47), it will be important to establish the specific physiological function of the FHL2 regulation of AP-1 activity and whether this activity may be coupled to the stimulation of the Rho-based signaling system. Finally, the recent finding that FHL2 may operate as an adaptor protein to couple metabolic enzymes to sites of high-energy consumption in the cardiac sarcomere (48) indicates that this LIM-only protein may have pleiotropic functions depending on its subcellular localization. Our experiments provide an important clue on the physiological significance of the nuclear-cytoplasmic shuttling of FHL2.…”
Section: Resultsmentioning
confidence: 99%
“…Because FHL2 has been shown to be implicated in the transmission of Rho-induced signals (47), it will be important to establish the specific physiological function of the FHL2 regulation of AP-1 activity and whether this activity may be coupled to the stimulation of the Rho-based signaling system. Finally, the recent finding that FHL2 may operate as an adaptor protein to couple metabolic enzymes to sites of high-energy consumption in the cardiac sarcomere (48) indicates that this LIM-only protein may have pleiotropic functions depending on its subcellular localization. Our experiments provide an important clue on the physiological significance of the nuclear-cytoplasmic shuttling of FHL2.…”
Section: Resultsmentioning
confidence: 99%
“…One possible explanation for the dual role of FHL2 in a transcription or regulating signaling pathway might be that FHL2 acts to stabilize the functional complexes as a type of bridging factor. This explanation was supported by the fact, like that the formation of a ternary complex by FHL2, CBP/ p300, and b-catenin could synergistically activate ARmediated transcription (28), and that FHL2 interacts with titin, a protein that plays a crucial role as organizer of the sarcomere, and functions as an adaptor molecule that links the metabolic enzymes MM-creatine kinase, adenylate cyclase and phosphofructokinase to titin, thereby helping to recruit metabolic enzymes needed for energy provision during muscle contraction (40). In dramatic contrast, we observed that FHL2 acts as a competitor of E47 for Id2 binding and subsequently allows E47 to recruit to its target DNA and execute its transcriptional activity ( Figure 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…In the cytoplasm, FHL proteins have been shown to be localized to cytoskeletons such as actin stress fibers (6, 9, 52, 65), focal adhesions (6,29,65), and the Z-discs (9, 27, 29) of cultured cells and muscle tissues. Recent reports indicate that FHL3 inhibits ␣-actinin-mediated bundling of actin fibers in vitro (9), and FHL2 mediates the targeting of the metabolic enzymes creatine kinase, adenylate kinase, and phosphofructokinase to the elastic filament protein titin in cardiomyocytes (27). In the nucleus, several FHL family members have been demonstrated to bind directly to DNA-binding transcriptional factors and to function as transcriptional coregulators.…”
Section: Discussionmentioning
confidence: 99%